Quench of molten copper and eutectic mixture in natural seawater. (June 2019) - Chang, Yu-You; Fu, Ben-Ran; Pan, Chin
Highlights: The quenching of molten materials in de-ionized water and seawater is studied. No fragmentation in the case of molten copper owing to its high surface tension. The quench of BTOP with small surface tension results in extensive fragmentation. The quench in seawater yields debris of larger sizes with rough surfaces. Intensive interactions between BTOP melts and seawater owing to the complex ions. Abstract: The interaction of molten materials with coolant is of significant fundamental interest and is of paramount importance for nuclear safety and material processing as well. This study explores the quenching of melts of copper spheres and a eutectic mixture of bismuth trioxide and tungsten trioxide (BTOP) in de-ionized water and natural seawater through visualization using a high-speed video camera. The results show no fragmentation in the case of molten copper owing to its high surface tension, while the quench of BTOP in de-ionized water and seawater results in extensive fragmentation. The fragmentation in seawater is characterized by a greater fraction of larger debris than that in the de-ionized water. Moreover, the examination of the debris quenched in seawater using scanning electron microscopy reveals a rougher surface, which demonstrates intensive interactions between the BTOP melts and the seawater owing to the complex ions there.